Breeding biology of the Yellow Wagtail Motacilla f. flava in shore meadows in north-eastern Scania - Flyckt, Greger (Ornis Svecica, 1999)
The subspecies Motacilla flava flava of the Yellow Wagtail has shown a decreasing breeding population trend in southern Sweden. A contributory cause could be the extensive use of wetlands, the most preferred breeding habitat. This habitat is successively disappearing from modern Swedish farmland. To get more information about the breeding biology in southern Sweden a study was started in 1991. Data from a total of 81 nests from shore meadows were collected during 1991—1996. The birds showed a preference for breeding in grazed areas (63–70%) in comparison with mowed meadows. The average breeding success in grazed areas differed from the mowed areas (4.26 vs. 4.68 fledged young per nest). Out of 13 unsuccessful breeding attempts, 8 failures were directly caused by grazing cattle.